Um Panorama das Pesquisas Científicas focado no ENCompIF: Um Mapeamento Sistemático - Fernandes, Filipe; Pereira, Otacílio; da Silva, Loham (Anais do Encontro Nacional de Computação dos Institutos Federais (ENCompIF), 2020)
Context: The Federal Education network reached the mark of 562 units and plays an important role so that all people have access to the country's scientific and technological achievements. Understanding the performance of a certain scientific community allows its members to organize their decision making about what actions and directions to take in a certain context. Goal: Thus, the goal of this work is to present a Systematic Mapping (SM) of papers published in the National Computing Meeting of Federal Institutes (ENCompIF), with the purpose of characterizing the state of the art of computer research carried out by institutions of the Federal Education network. Method: The search strategy for this SM was defined as primary studies published in ENCompIF in the period between 2014 and 2019, applying inclusion and exclusion criteria. Results: In the six editions of ENCompIF, 112 studies were published. When applying the inclusion and exclusion criteria, all studies were selected for analysis. Conclusions: From primary studies analyzed, 46.43% proposed software development as a solution; 19.64% and 13.39% of the studies work in Informatics in Education and Games and Digital Entertainment, respectively. Despite the slight decline in publications over the years, the community has intensified efforts to engage students, as well as developing solutions to support the teaching and learning process through computational solutions.